METAPHYSICAL FOUNDATIONS OF AI ETHICS: A THOMISTIC-ISLAMIC DIALOGUE ON HUMAN DIGNITY AND MORAL AGENCY IN THE DIGITAL AGE - Neonnub, Patricius; Kosat, Octovianus (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This paper explores the ontological foundations of moral agency in the context of Artificial Intelligence (AI) by engaging two metaphysical traditions: Thomistic natural law and Islamic metaphysical ethics. While contemporary AI ethics is often shaped by secular frameworks such as utilitarianism and deontology, these approaches frequently lack the metaphysical depth needed to address fundamental questions of human dignity, intentionality, and responsibility. Drawing from actus essendi, lex aeterna, fitrah, and ʿaql, the study demonstrates that both traditions affirm moral agency as rooted in the human being’s participation in a transcendent moral order. In contrast, AI, as a non-rational artifact lacking teleology and metaphysical substance, cannot be considered a moral agent. Using a comparative-philosophical method, the paper proposes a transcultural ethical framework that re-centers AI governance on human dignity, ecological responsibility, and the common good. This framework contributes to global sustainability discourse by integrating Islamic knowledge and classical philosophy to guide ethical innovation in the digital age.